Constructivist-Based Arabic Reading Pedagogy in a Heterogeneous Student Context: Insights from Ma'had IAIN Kerinci - Ayumi, Nadila Mi; Yul, Widiya; Andrian, Riko (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
This study investigates the instructional strategies employed by Arabic language educators in teaching reading skills (mahārah al-qirā’ah) to students at Ma'had IAIN Kerinci, who possess diverse educational backgrounds. Specifically, it explores how teachers adapt their pedagogy to students' prior Arabic grammar knowledge, particularly among those with pesantren (Islamic boarding school) experience. Grounded in constructivist learning Theory, this qualitative research adopts a phenomenological approach involving classroom observations and in-depth interviews with six instructors and twelve students over four months. Data were thematically analyzed to capture recurring pedagogical patterns and learner experiences. The findings reveal that the constructivist approach is more effective in advanced-level classes, as students with prior grammatical knowledge actively engage in meaning construction. A key strategy identified is the use of i'rāb (grammatical analysis), which enhances students' ability to decode and comprehend Arabic texts. The study underscores the pedagogical value of i'rāb within a constructivist framework and highlights the necessity of aligning instructional strategies with students' linguistic backgrounds. These insights contribute to the development of context-sensitive Arabic reading instruction in heterogeneous academic settings